IMPLEMENTASI AKAD WADI’AH PADA PRODUK TABUNGAN FAEDAH DALAM MENINGKATKAN JUMLAH NASABAH DI BANK SYARIAH INDONESIA - Moch. Zaenal Azis Muctharom (Jurnal Ekonomi Syariah Darussalam, 2025)
The aim of this research is to analyze the implementation of the wadi’ah contract in the Faedah Savings product at Bank Syariah Indonesia and efforts to increase the number of customers at Bank Syariah Indonesia Bojonegor. This research uses data collection methods through interviews, observation and documentation. This research uses a qualitative type of research using SWOT analysis. The results of this research show that Faedah Savings is a savings account for individual customers who use the deposit principle, who want convenience in daily transactions, his product uses the wadi’ah yad dhamanah contract. Meanwhile, there are 3 methods to increase the number of customers, namely personal selling, advertising and free. Kata Kunci: Implementasi, Tabungan Faedah, Upaya Meningkatkan Jumlah Nasabah